The synthetic phospholipid C8-C1P determines pro-angiogenic and pro-reparative features in human macrophages restraining the proinflammatory M1-like phenotype - Ortiz Wilczyñski, Juan Manuel; Mena, Hebe Agustina; Ledesma, Martin Manuel; Olexen, Cinthia Mariel; Podaza, Enrique; Schattner, Mirta; Negrotto, Soledad; Errasti, Andrea Emilse; Carrera Silva, Eugenio Antonio (Frontiers in Immunology, 2023)
Monocytes (Mo) are highly plastic myeloid cells that differentiate to macrophages after extravasation, playing a pivotal role in the resolution of inflammation and regeneration of injured tissues. Wounds-infiltrated monocytes/macrophages are more pro-inflammatory at early timepoints, while showing anti-inflammatory/pro-reparative phenotypes at later phases, with highly dynamic switching depending on the wound environment. Chronic wounds are often arrested in the inflammatory phase with hampered inflammatory/repair phenotype transition. Promoting the tissue repair program switching represents a promising strategy to revert chronic inflammatory wounds, one of the major public health loads. We found that the synthetic lipid C8-C1P primes human CD14+ monocytes, restraining the inflammatory activation markers (HLA-DR, CD44 and CD80) and IL-6 when challenged with LPS, and preventing apoptosis by inducing BCL-2. We also observed increased pseudo-tubule formation of human endothelial-colony-forming cells (ECFCs) when stimulated with the C1P-macrophages secretome. Moreover, C8-C1P-primed monocytes skew differentiation toward a pro-resolutive-like macrophages, even in the presence of inflammatory PAMPs and DAMPs by increasing anti-inflammatory and pro-angiogenic gene expression patterns. All these results indicate that C8-C1P could restrain M1 skewing and promote the program of tissue repair and pro-angiogenic macrophage.